2019
DOI: 10.1007/s11664-019-07731-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Quaternary Barrier InAlGaN/GaN/AlGaN Double-Heterojunction High-Electron-Mobility Transistors (HEMTs) for High-Speed and High-Power Applications

Abstract: We report direct current (DC) and microwave performance of a 50-nm gate length (L g) quaternary-based InAlGaN/GaN/AlGaN high-electron-mobility transistor (HEMT) on SiC substrate with SiN passivation and by using a Tgate. The proposed HEMT structure is simulated using industry-standard Synopsys Sentaurus technology computer-aided design (TCAD). The regrown n++ GaN source/drain ohmic contacts show a peak drain current density (I dmax) of 2.9 A/mm along with low on-resistance of 0.49 X mm. A record power gain cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…6 Among various architectures, junction-barrier Schottky diodes, highelectron-mobility transistors (HEMTs), low-voltage power fieldeffect transistors (FETs) with low voltages, and high-frequency devices are receiving attention as near-future power devices. 7 Si plays a dominant role in power electronics systems. However, the relatively narrow bandgap of Si (1.1 eV at room temperature) leaves little potential for the further advancement of Si application in these systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Among various architectures, junction-barrier Schottky diodes, highelectron-mobility transistors (HEMTs), low-voltage power fieldeffect transistors (FETs) with low voltages, and high-frequency devices are receiving attention as near-future power devices. 7 Si plays a dominant role in power electronics systems. However, the relatively narrow bandgap of Si (1.1 eV at room temperature) leaves little potential for the further advancement of Si application in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…6 Among various architectures, junction-barrier Schottky diodes, high-electron-mobility transistors (HEMTs), low-voltage power field-effect transistors (FETs) with low voltages, and high-frequency devices are receiving attention as near-future power devices. 7…”
Section: Introductionmentioning
confidence: 99%
“…One novel approach, initially suggested by Ketteniss et al and subsequently confirmed, involves using a thin quaternary AlInGaN barrier layer that introduces polarization engineering between the barrier and the GaN channel, enabling E-mode operation [11,12]. Quaternary nitride has garnered significant attention as an alternative to AlGaN barrier layers due to its promising DC and RF performance, including the ability to utilize high aluminum content, leading to increased spontaneous polarization induced by high 2DEG carrier density (ns > ~1.8×10 13 cm -2 ) and high mobility (µ > ~ 1800 cm 2 /V s) [13][14][15]. Traditionally, since 1991, HEMT transistors have been designed and fabricated with a single barrier layer [16].…”
Section: Introductionmentioning
confidence: 99%
“…For improved device power performance, enhancing the breakdown voltage is a must and several technologies have been proposed and developed to meet this goal. GaN HEMT breakdown voltage is enhanced by the incorporation of GFP, 10 source field plate (SFP), 11 drain field plate (DFP), 12 multiple grating field plates, 13 buried p-type layer 14 or acceptor-type doping of the GaN buffer, 15 double heterojunction back barrier 16,17 enabling better carrier confinement and filleted gate geometry to address reliability issues. 18,19 However, most research work focuses on GFP technology as it turns out to be an effective method for improving breakdown performance due to reduction and redistribution of the electric field in the critical drain access region without changing the epitaxial stack.…”
Section: Introductionmentioning
confidence: 99%